DAMPAK KERAGAMAN SUMBERDAYA PORTOFOLIO ALIANSI TERHADAP INOVASI DENGAN PEMODERASI KETIDAKPASTIAN PASAR DAN PENGALAMAN ALIANSI - Zuwina Miraza; Hafriz Rifki Hafas (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The main objective of this research is to provide insight to companies about the importance of forming an alliance portfolio in the development of sustainable innovation. The method used is Multiple Regression Analysis using SPSS 19. The sample was drawn from the entire population of Large and Medium Enterprises who never committed a strategic alliance and are in Medan. Based on the analysis found that the diversity of resources alliance portfolios provide significant pegaruh to business innovation for medium and large companies in the city of Medan. But in fact not only the diversity of resource variables that affect the alliance portfolio creation process of innovation, but also variable experience in making alliances and their high level of market uncertainty in Medan.Keywords: Diversity of Resources, Alliance Portfolio, Innovation, Market Uncertainty, Alliance experience.